2016
DOI: 10.1007/s10517-016-3317-2
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factors (IGF) and IGF-Binding Proteins (IGFBP) in the Serum of Patients with Ovarian Tumors

Abstract: IGF-1, IGF-2, and IGFBP-1,2,3 were assayed in blood serum of patients with malignant ovarian tumors (n=44), borderline ovarian tumors (n=11), and benign ovarian tumors (n=12) as well as in healthy women (n=33). In blood serum of patients with malignant ovarian tumors, the level of IGF-1 was lower and IGFBP-1 was higher than in other groups. In patients with malignant and borderline ovarian tumors, the level of IGFBP-2 was higher than in healthy women and in patients with benign ovarian tumors. There was no cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…To further know how miR‐19a‐3p regulates the oncogenesis of ovarian cancer cells, we predicted the potential downstream targets of miR‐19a‐3p by the algorithms of TargetScan and PicTar. Among the potential targets, IGFBP‐3 was selected for further study because it is a well‐known tumor suppressor and it is downregulated in patients with malignant ovarian cancer …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further know how miR‐19a‐3p regulates the oncogenesis of ovarian cancer cells, we predicted the potential downstream targets of miR‐19a‐3p by the algorithms of TargetScan and PicTar. Among the potential targets, IGFBP‐3 was selected for further study because it is a well‐known tumor suppressor and it is downregulated in patients with malignant ovarian cancer …”
Section: Resultsmentioning
confidence: 99%
“…Among the potential targets, IGFBP-3 was selected for further study because it is a well-known tumor suppressor and it is downregulated in patients with malignant ovarian cancer. 28 Base-pairing complementation showed that the 3′ untranslated region (UTR) of IGFBP-3 contains a putative site that is conserved among species and the site has significant complementarity with the seed sequence of miR-19a-3p ( Figure 5A). We next examined the interaction between miR-19a-3p and 3′-UTR of IGFBP3 mRNA by the dual-luciferase reporter assay.…”
Section: Igfbp-3 Is a Target Gene Of Mir-19a-3pmentioning
confidence: 99%
“…Recent studies also validated IGFBPs' role in the diagnosis and prognosis prediction in some solid tumor including nasopharyngeal carcinoma, ovarian cancer, pancreatic cancer, etc. (4246). Despite the huge development of IGFBPs as biomarkers in cancer, there have been a number of studies focusing on the utility of IGFBPs as biomarkers in autoimmune diseases (Table 1).…”
Section: Igfbps As Biomarkers In Autoimmune Diseasesmentioning
confidence: 99%
“…Inhibition of IGF signaling by IGFBP3 was shown to result in increased sensitivity to CDDP in CDDP-resistant lung cancer cells [ 8 ]. In spite of the fact that many studies have characterized the roles of six IGFBPs (IGFBP1-6) in the IGF signaling pathway [ 10 , 11 , 12 ], studies on the acquisition of CDDP-resistance mediated by IGFBPs are scanty. Moreover, other candidate proteins have also been reported to be involved in tumor growth and/or therapeutic responses; examples include, but not limited to, insulin-like growth factor binding protein 5 (IGFBP5) [ 13 ], major histocompatibility complex, class II, DQ alpha 2 (HLA-DQA2), [ 14 ] carboxypeptidase E (PE) [ 15 ], and PLXDC2 (CDNAFLJ45742fis) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%